Epidemic Typhoid in Vietnam: Molecular Typing of Multiple-Antibiotic-Resistant Salmonella enterica Serotype Typhi from Four Outbreaks - Connerton, Phillippa (American Society for Microbiology, 2000)
Multidrug-resistant Salmonella enterica serotype Typhi isolates from four outbreaks of typhoid fever in southern Vietnam between 1993 and 1997 were compared. Pulsed-field gel electrophoresis, bacteriophage and plasmid typing, and antibiotic susceptibilities showed that independent outbreaks of multidrug-resistant typhoid fever in southern Vietnam are caused by single bacterial strains. However, different outbreaks do not derive from the clonal expansion of a single multidrug-resistant serotype Typhi strain.